Home-Based Exercise Improves Fitness and Exercise Attitude and Intention in GDM Women - Halse, Rhiannon; Wallman, K.; Dimmock, J.; Newnham, J.; Guelfi, K. (Lippincott Williams & Wilkins, 2014)
© 2014 American College of Sports Medicine METHODS: Forty women (28.8 ± 0.9 weeks gestation) were randomized to either a supervised, home-based exercise program, combining continuous steady-state and interval cycling at various intensities, in combination with unsupervised moderate intensity aerobic activity and conventional diabetic management (EX; n = 20), or to conventional management alone (CON; n = 20). The program began following diagnosis until week 34 of pregnancy (mean duration of training 6 ± 1 weeks). RESULTS: Mean compliance to the training program was 96%. Maternal aerobic fitness, and attitude and intentions towards exercise were improved in response to the home-based exercise intervention compared with CON (p < 0.05). No differences were observed between groups with respect to maternal weight gain or obstetric and neonatal outcomes (p > 0.05). CONCLUSION: A home-based exercise program of 6 ± 1 weeks in duration commenced following diagnosis of GDM can improve aerobic fitness and attitude and intentions towards exercise, with no adverse effect on maternal and neonatal pregnancy outcomes. PURPOSE: To determine the effect of a home-based cycling program for women recently diagnosed with gestational diabetes mellitus (GDM) on aerobic fitness, weight gain, self-reported mobility, attitude and intentions towards maternal exercise, and obstetric and neonatal outcomes.